2022 IEEE Symposium Series on Computational Intelligence (SSCI) 2022
DOI: 10.1109/ssci51031.2022.10022087
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Design Modifiers

Abstract: Evolutionary Developmental biology (EvoDevo) is a process of directed growth whose mechanisms could be used in an evolutionary algorithm for engineering applications. Engineering design can be thought of as a search through a high-dimensional design space for a small number of solutions that are optimal by various metrics. Configuring this search within an EvoDevo algorithm may allow developmental processes to provide a facility to give more immediate, localised feedback to the system as it grows into its fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Artificial growth in generative systems can vary greatly in implementation, but all must come to a point where they stop growing. This is typically achieved with some hardcoded limit, often even built into the mechanism that generates phenotypes, or as a limit set by a user [14,13,11]. However, to take full advantage of the evolutionary emergence of properties, it may prove helpful to give more control to the evolved generative systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial growth in generative systems can vary greatly in implementation, but all must come to a point where they stop growing. This is typically achieved with some hardcoded limit, often even built into the mechanism that generates phenotypes, or as a limit set by a user [14,13,11]. However, to take full advantage of the evolutionary emergence of properties, it may prove helpful to give more control to the evolved generative systems.…”
Section: Introductionmentioning
confidence: 99%
“…GRNs can be emulated within generative systems through computational structures such as feedforward neural networks and have been successfully implemented for multi-objective problems in [11]. That contribution used a fixed number of development steps and did not investigate the controlled stopping of growth.…”
Section: Introductionmentioning
confidence: 99%
“…Price et al [11] have demonstrated the use of Devo processes to create a bracket component. Recent work shown in [12] demonstrated the use of EvoDevo to optimize the structure of the Warren truss problem (bridgelike structure). In this approach, an artificial gene regulatory network (GRN) regulates the growth from an initial structure (seed) to the final solution during the Devo process.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to traditional evolutionary processes (where random initial starting points are often chosen), in the EvoDevo process a seed is required to start the process. The concept of a seed, introduced in [12], is defined as an initial solution (structure) whose main requirement is to connect the supports and the external load. In previous work, the seed provided to the EvoDevo process is hand-designed and its quality is relatively good [12] where quality in this context refers to the behaviour of a structure of having a subjective low volume and low strain energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation